Implementation Of Active Learning Model In Improving Students' Learning Motivation And Understanding In Pai Learning: A Case Study At Sman 1 Jonggat - Siti Ria Farhaeni (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Islamic Religious Education (PAI) learning in many educational units is still dominated by lecture methods, making it less able to stimulate student activity, motivation, and conceptual understanding. This condition emphasizes the need to implement a learning approach that allows students to be more intensively involved in the process of constructing knowledge. This study aims to describe in depth the implementation of the Active Learning model through Problem Based Learning (PBL) on the material of Mawaris and analyze its influence on the motivation and understanding of students in class XII F10 SMAN 1 Jonggat. This study used a qualitative approach with a case study design. The results of the study indicate that the implementation of Active Learning through PBL was effective and provided space for students to actively participate in discussions, analyze cases, and construct understanding independently. Students showed increased motivation, courage to express opinions, and the ability to solve Mawaris problems. Learning became more dialogic, contextual, and meaningful. Thus, Active Learning has proven relevant in improving the quality of PAI learning, especially on materials that require reasoning and conceptual understanding.